Correlation between Neutrophil-to-Lymphocyte Ratio with Disease Severity in Diabetic Patients with COVID-19 at Tertiary Referral Hospital in Indonesia - Cupuwatie Cahyani, -
Abstract Coronavirus disease 2019 (COVID-19) is highly transmissible and spreads quickly with the clinical presentation varies from asymptomatic to severe respiratory symptoms, even leading to death. Diabetes mellitus is one of the main comorbidities contributing to worsening the COVID-19 cases. Increased Neutrophil-to-Lymphocyte Ratio (NLR) is considered as an early warning of COVID-19 severity. This study evaluated the correlation between NLR with disease severity at admission in diabetic patients with COVID-19 at a tertiary referral hospital in Indonesia. The authors performed a retrospective study using secondary data from medical records of diabetic inpatients with COVID-19 from May to September 2020. The demographic data were collected from the medical record and the hematologic parameter from the laboratory. NLR was calculated by dividing the absolute neutrophils counts by the absolute lymphocyte counts. The data was analyzed with a significance level of p < 0.05. Study subjects consisted of 100 non-severe cases and 128 severe cases. The median NLR of severe and non-severe groups was 9.7 vs. 5.22 (p < 0.001). The correlation coefficients of NLR with disease severity were 0.52 (p < 0.001). The calculated Area Under the Curve (AUC) of the ROC analysis for the NLR was 0.803 (cut-off: > 6.15; p < 0.001) with sensitivity 91%, specificity 64%, negative predictive value 16%, and positive predictive value 75.82%. NLR had a significant positive correlation with disease severity at admission in diabetic patients with COVID-19. As simple, rapid, and cost-effective biomarkers, NLR can help clinicians identify potentially severe cases early, conduct early triage, and initiate effective management in time so the progress of disease severity should be possibly prevented.